2015
DOI: 10.15386/cjmed-445
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the sonication process for meloxicam nanocrystals preparation

Abstract: Background and aimsMeloxicam, a widely recommended AINS, presents poor water solubility, which limits its bioavailability and effect onset. The objective of this study is the investigation of the most important factors that influence the efficiency of sonication in the preparation of meloxicam nanocrystals.MethodsThe effects of crucial technological sonication parameters (amplitude, time and applied cycle) on the crystal sizes and dissolution were investigated using a central composite experimental design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The comparison of continuous and intermittent sonication revealed no advantage of pulsed processing at room temperature, and even a disadvantage at lower temperature. To the authors' knowledge, studies on nanosuspensions described in the publicly available literature focus mostly on one chosen mode and in one found example there was no significant difference between the variants [61]. However, the present results are in agreement with the case studies of large particles crystallization reviewed by Ruecroft et al, according to which continuous insonation reduces particle sizes, while short ultrasound bursts favor crystal growth [23].…”
Section: Lasp-study Of Factors and Optimization: Influence Of Drug Concentration Stabilizer Amount Mixing And Feeding Speedsupporting
confidence: 90%
See 1 more Smart Citation
“…The comparison of continuous and intermittent sonication revealed no advantage of pulsed processing at room temperature, and even a disadvantage at lower temperature. To the authors' knowledge, studies on nanosuspensions described in the publicly available literature focus mostly on one chosen mode and in one found example there was no significant difference between the variants [61]. However, the present results are in agreement with the case studies of large particles crystallization reviewed by Ruecroft et al, according to which continuous insonation reduces particle sizes, while short ultrasound bursts favor crystal growth [23].…”
Section: Lasp-study Of Factors and Optimization: Influence Of Drug Concentration Stabilizer Amount Mixing And Feeding Speedsupporting
confidence: 90%
“…Therefore, it must be concluded that a single equation derived from linear regression principles is unable to model and predict the relationship between precipitation-sonication parameters and nano/microsuspension particle size. To the authors' knowledge, in the publicly available literature on sonoprecipitation employing DoE such situation has not yet been reported, possibly because other types of factors than sonication energy and feed concentration are mostly evaluated with this methodology [47,55,57,59,61,67,[69][70][71][72][73][74]. One exception is the work of Sharma et al, who analyzed the effect of drug concentration, injection rate and sonication time using Box-Behnken design with results differing from the present report, i.e., interaction effect was insignificant and both concentration and time displayed negative linear effects modified by positive quadratic effects [75].…”
Section: Lasp+sonication Study Of Factors Using Doe: Influence Of Drug Concentration Sonication Time and Amplitudementioning
confidence: 99%
“…23 Hence, to prevent curcumin aggregation and prepare stable drug nanocrystals, important processing conditions and formulation parameters involved in the preparation were screened and optimized. 47 We found that using 2 mg/mL of CH aqueous solution as an antisolvent with curcumin prepared in ethanol resulted in stable drug nanocrystals after sonication at 150 W/ cm 2 for 30 min. The drug nanocrystals (CH 1 @CUNCs) were characterized for their particle size, PDI, surface charge, and shape.…”
Section: ■ Discussionmentioning
confidence: 86%
“…The aggregated nanocrystals do not represent suitable particle core for LBL-coating . Hence, to prevent curcumin aggregation and prepare stable drug nanocrystals, important processing conditions and formulation parameters involved in the preparation were screened and optimized . We found that using 2 mg/mL of CH aqueous solution as an antisolvent with curcumin prepared in ethanol resulted in stable drug nanocrystals after sonication at 150 W/cm 2 for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Nanonization strategies have been shown to be very promising approaches to improve the dissolution. 10,11 The use of nanosuspensions is one attractive nanoscience approach for the intravenous (iv) administration of MX, and the reduced particle size and large specific surface area of nanosuspensions lead to an increase in the dissolution and saturation solubility of loaded drugs. [12][13][14] Compared with some other nanostructured carriers such as micelles, 15,16 gold nanoparticles, 17,18 and nanoemulsion, 19 nanosuspensions have a number of advantages including reduced toxicity, simple formulation, and established preparation technology.…”
Section: Introductionmentioning
confidence: 99%